1st European Academy for Healthcare Leaders: high training on leadership to manage health systems. (13th November 2019) - Villani, L; Frisicale, E M; Parente, P; Cacciatore, P; Carini, E; Gentili, A; Grossi, A; Pezzullo, A M; Favaretti, C; Ricciardi, W
Abstract: Background: Nowadays having leadership skills is critical to manage healthcare systems. The World Health Organization Collaborating Centre on Health Policy, Governance and Leadership organized the 1st European Academy for Healthcare Leaders in Rome from 15th to 17th November 2018. Senior officials of the Ministries of Health of 16 Members Countries of the WHO European Region attended and actively participated to the event, led by experienced Italian and European experts. The Academy could be considered a moment of high training on leadership and governance of health systems. Objectives: The event was aimed at creating effective networks among participants to share ideas and strategies to improve leadership skills, providing practical tools to be applied in healthcare systems and to develop a common and transferrable leadership framework in Europe. Frontal lectures and interactive workshops covered three main areas: leadership skills, current challenges of health systems and sustainability of health systems today. Results: The 3-days event gave the opportunity to discuss the main issues in Public Health highlighting how to be an effective leader in healthcare. Leadership should enable the translation of knowledge into productive action pathways, providing health equity and improving population's health. At the end of the event, participants filled a survey and the results showed high satisfaction about contents (100% out of 16 participants). Conclusions: Health systems need to change in order to face the formidable challenges of our times. This event empowered the participants in order to support the creation of strategies and to develop leadership tools to apply at country level. The experiences, ideas and good practices shared during this event strengthened a collaborative network and have been useful to identify common goals and solutions. Key messages: These kinds of events are fundamental to improve knowledge about leadership in healthcare. Leadership should have a major role to play in healthcare worldwide.